The Effectiveness of Trichoderma sp. on Organic Cayenne Pepper Production - Eko Prihatiningrum, Andriani; Wach, Abdul; ., . (International Journal of Engineering and Technology, 2018)
Trichoderma sp. has the properties as an agent of controlling plant diseases and may also serve to provide nutrients for cayenne pepper. Knowing the excellent nature of Trichoderma sp. leads to itssignificance on doing a research on optimizing the role of Trichoderma sp. for the organic cayenne pepper. This study aims to find out doses of Trichoderma sp. needed for cayenne pepper best growth. Trichoderma sp. with a total population of 5.7 x 108cfu/cc was given to compost.Â Every 500 g of compost, was given 0, 5, 10, 15,20 cc Trichoderma sp.The study was conducted in a green house from March to September 2016. The experiment used completely randomized design with 5 treatments (Trichoderma dose of 5 ccÂ of compost, 10 , 15 , 20 cc and without Trichoderma), and repeated 6 times. The results show that the higher the dose was given, the better the plant grew. The number of leaves and flowers of cayenne pepper increased, and the best one was on the plant with 20 cc of compost. Â